Anthropic disasters in Peruvian Traditions - Huertas Vallejos, Lorenzo (2019)
The disasters that alter the social development are of two types: natural and social. Ricardo Palma registered both types phenomenons in his Peruvian Traditions and also in his epistles. This article examines disasters caused by the man or anthropics in the work of Palma. For this inquiry, we have selected the tradition “Los Caballeros de la Capa. Crónica de una guerra civil” which deals with an event that marked the destiny of Peru: the war between Francisco Pizarro and Diego de Almagro.